Detection of Salmonella sp. on Bulk Meatballs and Packaged Meatballs at Sepanjang Market, Sidoarjo - Rahmania Zain; Sri Hidanah; Ratna Damayanti; Sunaryo Hadi Warsito (Journal of Applied Veterinary Science And Technology, 2021)
Background: Bacterial contamination in food can cause congenital diseases in the form of infections. Meatballs are one of the foods that are in demand by the public and foods that can be contaminated with salmonella bacteria. Detection of Salmonella sp bacteria can determine the quality of bulk meatballs and packaged meatballs. Salmonella sp bacteria should not contaminate the meatballs according to the quality requirements of the BSNI (Badan Standarisasi Nasional Indonesia). Purpose: To determine the contamination of Salmonella sp bacteria in bulk meatballs and packaged meatballs sold at Sepanjang market, Taman District, Sidoarjo Regency. Methods: The Salmonella sp. test on meatballs was carried out in four stages, pre-enrichment using Buffered Pepthone Water solution, enrichment using Tetrathionate Brothbase solution, isolation using Salmonella Shigella Agar media, and biochemical testing using Triple Sugar Iron Agar media. The samples used were 10 samples each. Result: The test proved that 20% of the samples were positively contaminated with Salmonella sp. both on bulk meatballs and on packaged meatballs. Conclusion: Food hygiene and sanitation must be applied properly and correctly in every process because food products circulating in public, especially meatball products, can avoid microbial contamination and be safe for consumption.